Effect of Grinding and Polishing Protocols on Surface Roughness, Flexural Strength, and Phase Transformation of High-Translucent 5 mol% Yttria-Partially Stabilized Zirconia - Phatphutthitham, Chatnarong; Niyatiwatchanchai, Boondarick; Rujiraprasert, Phakvalunch; Tagami, Junji; Osathanon, Thanaphum; Srijunbarl, Anucharte; Singthong, Thawanrat; Suriyasangpetch, Sarat; Nantanapiboon, Dusit (European Journal of Dentistry, 2024)
Objectives This study evaluated surface roughness, biaxial flexural strength, and phase transformation of 5Y-PSZ after grinding and polishing with different protocols.Material and Methods Two commercial 5Y-PSZ, Lava Esthetic (L) and Cercon xt (C), were used and divided into 3 groups: LC and CC represented unpolished control groups; LE and CE were polished with protocol I (EVE DIASYNT® PLUS HP following with EVE DIACERA RA); and LJ and CJ were polished with protocol II (Superfine diamond bur following with Jota ZIR Gloss polishing kit). Surface roughness was evaluated after polishing step-by-step with a contact-type profilometer. After high-gross polishing, the specimens were subjected to biaxial flexural strength test, crystallographic microstructure analysis using an X-ray diffractometer (XRD), and surface micro-topography using scanning electron microscopy (SEM).Statistical Analysis Surface roughness differences after each step and biaxial flexural strength between groups were evaluated with one-way ANOVA, followed by Bonferroni post-hoc analysis. Changes in surface roughness across four different time points within groups were assessed using one-way repeated measures ANOVA, followed by Bonferroni post-hoc analysis.Results After high-gross polishing, both polishing protocols showed significantly lower surface roughness than the grinding group (p < 0.05). The LE and CE groups exhibited the highest surface roughness values, which were significant differences from the LJ and CJ groups (p < 0.05). The LE group showed significantly lower biaxial flexural strength compared to the LC group (p < 0.05). However, there was no statistically significant difference in the CE and CJ groups compared to the control group (p > 0.05). Furthermore, all polishing protocols did not change the phase transformation of zirconia.Conclusion Polishing protocol II provided a smoother surface than the protocol I after high-gross polishing, while the biaxial flexural strength of materials remained unaffected.
Keywords: zirconia; 5Y-PSZ; surface roughness; biaxial flexural strength